2020
DOI: 10.1103/physrevb.102.174405
|View full text |Cite
|
Sign up to set email alerts
|

Bulk and element-specific magnetism of medium-entropy and high-entropy Cantor-Wu alloys

Abstract: Magnetic Compton scattering, x-ray magnetic circular dichroism spectroscopy, and bulk magnetometry measurements are performed on a set of medium-(NiFeCo and NiFeCoCr) and high-entropy (NiFeCoCrPd and NiFeCoCrMn) Cantor-Wu alloys. The bulk spin momentum densities determined by magnetic Compton scattering are remarkably isotropic, and this is a consequence of the smearing of the electronic structure by disorder scattering of the electron quasiparticles. Nonzero x-ray magnetic circular dichroism signals are obser… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 95 publications
1
14
0
Order By: Relevance
“…A strong magnetic frustration due to the fluctuations of Mn and Cr magnetic moments and their antiferromagnetic coupling to Fe and Co is expected to significantly reduce the overall magnetic moment of the system since these atoms correspond to 50% of the structure. Recent X-ray magnetic circular dichroism (XMCD) studies on high entropy alloys showed that that the bulk magnetic moments can be strongly suppressed with increasing concentration of antiferromagnetically coupled elements in the solid solution 33 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A strong magnetic frustration due to the fluctuations of Mn and Cr magnetic moments and their antiferromagnetic coupling to Fe and Co is expected to significantly reduce the overall magnetic moment of the system since these atoms correspond to 50% of the structure. Recent X-ray magnetic circular dichroism (XMCD) studies on high entropy alloys showed that that the bulk magnetic moments can be strongly suppressed with increasing concentration of antiferromagnetically coupled elements in the solid solution 33 .…”
Section: Resultsmentioning
confidence: 99%
“…(3) Field dependence of the magnetization indicated that the material acts differently than magnetically homogeneous ferromagnetic material where the magnetic moment is expected to saturate with an increasing magnetic field. In general, many magnetic states such as ferromagnetism 3 , 20 , 46 , ferrimagnetism 14 , 33 , antiferromagnetism 12 , and paramagnetism 47 are present in high entropy alloys materials due to complex magnetic couplings of constituent 3d elements. Often subtle compositional changes in 4 and 5 element systems stabilize one magnetic phase over the other.…”
Section: Resultsmentioning
confidence: 99%
“…Billington et al [48] carried out a detailed study of the element specific magnetic properties of the Cantor alloy and certain Cantor alloy variants using a combination of magnetic Compton scattering, x-ray magnetic circular dichroism spectroscopy, and bulk magnetization measurements, noting significant discrepancies between computational and experimental results when examining magnetic moments. However, in compounds where computation and experiment disagreed, computational moments were much larger than experimental ones.…”
Section: Comparison Of Dft and Experimentsmentioning
confidence: 99%
“…Much work has been done regarding the mechanical properties of Cantor alloys [8][9][10][11][12][13] , as well as the magnetic properties of similar compounds 6,7,[14][15][16][17][18][19][20][21][22][23] , but fewer studies have examined the magnetic properties of the original CrMnFeCoNi alloy [24][25][26][27][28] . Of its component elements, Cr and Mn are antiferromagnetic with T N = 311 K 29 and T N = 100 K 30 respectively, while Fe, Co, and Ni are ferromagnetic with T C = 1043 K, T C = 1394 K, and T C = 631 K, respectively 31 .…”
Section: Introductionmentioning
confidence: 99%